2012
DOI: 10.1007/s10880-012-9315-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Posttraumatic Growth in Accidentally Injured Patients

Abstract: This study examined prevalence and predictors of posttraumatic growth in 180 accidentally injured patients of mainland China in their convalescence stage, investigating its relationships with demographic and accidental injury variables, personality, posttraumatic stress disorder (PTSD) symptoms, and coping styles. Our results showed that posttraumatic growth (PTG) presented mostly in the domain of Relating to Others and indicated that PTG was significantly related to marital status, educational level, personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 27 publications
4
34
4
2
Order By: Relevance
“…These findings were lower than previous results (Wang et al, 2013) in Chinese accident survivors at least one month after injury (M = 61.89, SD = 14.17). One possible reason for the difference in PTG may be that PTG takes time to develop.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…These findings were lower than previous results (Wang et al, 2013) in Chinese accident survivors at least one month after injury (M = 61.89, SD = 14.17). One possible reason for the difference in PTG may be that PTG takes time to develop.…”
Section: Discussioncontrasting
confidence: 88%
“…The Chinese version of the Posttraumatic Growth Inventory (PTGI-C; Wang, Wang, Wang, Wu, & Liu, 2013) was used to assess PTG. The PTGI-C is comprised of 20-items with 4 subscales: Relating to Others, New Possibilities, Personal Strength, and Appreciation of Life.…”
Section: Posttraumatic Growthmentioning
confidence: 99%
“…Posttraumatic stress disorder and PTG had common variance together based on canonical correlation analysis. This supports other research finding that the constructs within PTSD and PTG are interrelated (Bauwens and Tosone, 2014;Croft et al, 2013;Wang et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Wang et al (2013) showed that higher avoidance symptoms were associated with higher PTG. Bauwens and Tosone (2014) study revealed a statistically significant relationship between traumatic re-experiencing and appreciation for life.…”
Section: Relationship Between Ptsd and Ptgmentioning
confidence: 97%
“…The Cronbach α is 0.90 for the total score [24]. A reliable Chinese version of the PTGI has recently been validated [25]. …”
Section: Methodsmentioning
confidence: 99%